Assessment of fire damaged concrete structure - Nur Aishah , Omar @ Yahya (2012)
Forensic engineering is the application of science to the investigation of failure or performance problem. This project is about to study the effect and behaviour of concrete structure after exposed to fire and also to study about assessment of fire damaged concrete structure which is under the investigation of forensic engineering structure. This study involved the detail analysis of methodologies on assessment of fire damaged concrete structure which the information is from journal, book and article. Besides that, to know what the current method of assessment of fire damaged concrete structure, collaboration with a forensic engineering company, RNC Technology (M) Sdn. Bhd is conducted. From the collaboration, an interview was held with the experienced engineer and also two projects of fire damaged concrete structure were taken from their previous project to be the case study in this project. This study also discuss about the detail of the assessment including the testing method The case studies is discuss about the assessment of level of fire damage, whether the damage is slight damage, moderate damage or serious damage and also how the repair technique will be determine from the assessment of the investigation that made. The result shows that the different of case studies in term of different causes of fire and different level of damage of the concrete structure will apply different testing methods used and repair technique that used. Finally, based on the overall result of the case study, a general guideline of methodology's assessment of fire damaged concrete structure in forensic engineering investigation is proposed. This generai ' rnethodology is applicable for assessment of fire damaged concrete structure.